Malnutrition and Associated Risk Factors among Children 6–59 Months Old in the Landslide-Prone Bududa District, Eastern Uganda: A Cohort Study - Nahalomo, Aziiza; Iversen, Per O.; Andreassen, Bård A.; Natigo Kaaya, Archileo; Rukooko, Archangel B.; Tushabe, Gerald; Nateme, Nancy C.; Rukundo, Peter M. (Current developments in nutrition, 2022)
The United Nations Sustainable Development Goal 2.2 calls for an end to all forms of malnutrition. This might be derailed due to persistent landslide disasters in low-income countries like Uganda. Objectives: The prevalence of malnutrition and the impact of seasonal variations and associated factors were assessed among children aged 6– 59 mo in the landslide-affected households in Bududa District, eastern Uganda. Methods: A prospective cohort study using a 2-stage simple random technique was applied to select 422 households including 392 children during May–August (food-plenty season) 2019. After 6 mo, in January–March (food-poor season) 2020, 388 households and 366 children were assessed. Socioeconomic and demographic data were collected using structured questionnaires. Child malnutrition outcomes were defined according to WHO criteria. Factors associated with malnutrition outcomes were identified by bivariate and multivariate logistic regression. Results: Stunting, underweight, wasting, and overweight prevalences were 37.7%, 13.3%, 3.6%, and 4.3%, respectively, in the food-plenty season and 42.6%, 14.2%, 2.1%, and 2.7%, respectively, in the food-poor season. Residing in the landslide-affected sub-county increased the odds for stunting [adjusted OR (aOR): 1.68; 95% CI: 1.08, 2.59; P = 0.025] and underweight (aOR = 4.25; 95% CI: 1.10, 15.36; P = 0.032) for children in the food-plenty season. Child age, sex, breastfeeding status, a nonimproved drinking water source, migration of any household member, and parents’ education were significant risk factors in the food-plenty season. In the food-poor season, parents’ education status, loss of any household member, child sex, and child age were significant risk factors. Conclusions: Stunting and underweight were more prevalent in the food-poor season while wasting and overweight were more prevalent in the food-plenty season. With the exception of child age, child sex, and parents’ education, child malnutrition risk factors differed between food-plenty and food-poor seasons. There is a need to address seasonality factors in program interventions targeting children <5 y in landslide-prone areas.
Keywords: children; malnutrition; landslides; overweight; stunting; Uganda; wasting